Hubungan Tipe Pola Asuh Keluarga Dengan Kejadian Skizofrenia di Ruang Sakura RSUD Banyumas - Febrianti, Sandra; Wijayanti, Rahayu; Munjiyati (Jurnal Keperawatan Soedirman, 2009)
Correlation some factors in Indonesian for latest years cause increasing depression, especially schizophrenia. Base on the empirical, some factor has been come schizophrenia and it is pattern of family care for example. Bed family environment or historical children care have been cause a kid in schizophrenia. The schizophrenia was meaning psychological disturbance, whenever it’s important base life. This research was aimed to examine there are correlation between family care pattern with schizophrenia at Sakura Room of RSUD of Banyums. This research was non experimental with retrospektif study approach. Subject in this reearch were patien of schizophrenia and non schizophrenia which care at Sakura Room of RSUD Banyumas, since October 10 to October 20, 2008, and there were enough inclusion criterium and exclusion. Sampling method with applied purposive sampling. Sum of responden are 84 respondents (experiment group = 42 and control group = 42). The questionare was applied instrument which content 10 questions of otoriter care, permisive care and democratics care. chi square test was used to statistical test. Base on the univariat analysis provide that in gender were male produced 26 respondents (38,1%), adult age in criterium was purpose adult (18-34 years) of 35 respondents (83,3%), base on the education was shown premire schol of 19 respondents (45,2%). General describe of family care pattern provided that schizophrenia have been caused otoriter typr of 29 respondents (69,0%), permisive type of 7 respondents (16,7%), and democratic type of 6 respondents (14,3%). Base on the bivariat analysis show that there are correlation family care pattern with schizophrenia, and it was provide the probabilty value of p=0,018 was smaller than level of significance ?=0,05.